Developing a Multicultural Competency Assessment Tool for School Counselors - Rahmi, Siti; Saparov, Rashid; Koffi, Kouadio (International Journal of Research in Counseling, 2025)
In an increasingly diverse educational landscape, the role of school counselors in addressing students' cultural, racial, and social differences has become pivotal. This study aims to develop a valid and reliable multicultural competency assessment tool tailored for school counselors. Using a research and development approach, the instrument was constructed through literature review, expert validation, and empirical testing involving 200 practicing counselors from various educational settings. The results demonstrate high internal consistency and construct validity, revealing three core dimensions: cultural awareness, knowledge of multicultural issues, and responsive counseling skills. This tool serves as a strategic resource for evaluating and enhancing counselors’ readiness to support diverse student populations. Its implementation is expected to improve culturally responsive practices and inform professional training programs for future counselors.